Decision Support System for Scholarship Scheme Grant (Dermasiswazah Pelajar) - Mazlan, Sarah Iryna; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
Scholarships are payments offered on the basis of academic achievement or other accomplishments to fund the education of students. MAINJ is one of the organisations providing scholarships for students living in Johor who would like to pursue their studies at the mentioned university. This scholarship is specifically for student from Asnaf families who want to further their studies, the student scholarship scheme grant is an assistance that has been introduced. The purpose of developing this system is to facilitate the Johor Islamic Religious Council (MAINJ) to manage and handle scholarship scheme applications. It can also keep all application and applicant records systematically reducing the risk of physical data loss and also facilitating data retrieval. In addition, the system can increase the level of decision-making efficiency previously made by the manager to decide whether or not the applicant is eligible for this scholarship scheme grant. This system can directly assess whether the applicant is eligible or otherwise by using the Tree Decision method. The development of this system is guided by the Prototype model. Meanwhile, PhP programming language and MySQL database is used for system production. The web application system consists of five modules in total, namely login, data management, applications, reports, and evaluations. Users for this system consists decision maker, administrator and applicant (user). It is expected that this system will not only make it easier for MAINJ to manage application information and make decisions but also make it easier for applicants to apply and review the results.